Evaluating the Outcomes of Vocational Education Program in Abu Dhabi from a Project Management Perspective - Heikal, Moustafa Mamdouh (2014)
The paper examined the effectiveness of the evaluation method currently applied to measure the outcomes of the vocational education programs in Abu Dhabi. In-depth interviews were carried out with three managers and the documents of one of the biggest vocational institutes in Abu Dhabi were reviewed. It has been found that the current trend is using basic and conventional evaluation systems. Evaluating the outcomes of the programs is done as part of other evaluation processes and is limited to closure of the program. What differentiates the vocational programs is the impact of their outcomes on the community at large, represented by the employers and Tawteen Council. Therefore, the Multi-Objective Realization Approach (MORE) is proposed as an appropriate method for evaluation to be applied in Abu Dhabi Institutes. The MORE Approach will help in evaluating the effectiveness of the programs in addition to measuring their outcomes in relation to the stakeholders’ objectives and needs. The programs include delivering and assessing different types of diplomas to enhance the opportunities of local job seekers in finding jobs. By using the MORE evaluation framework, the outcomes evaluation of the programs will be extended beyond program closure. It has been found that the current evaluation method should include the number of graduates against the percentage of employment. It also should involve the competencies of the graduates against the skills required in the market. Moreover, the outcomes of the programs must include their impact the education levels. The proposed MORE method will help in increasing the possibility of achieving the strategic goals of both; the institute and its stakeholders. Therefore, this study focuses mainly on the outcomes of the evaluation methods in respect to stakeholders’ short and long term needs and objectives.